Impact of Problem-Based Learning on Student Achievement in Economics Course - Narmaditya, Bagus Shandy; Winarning, Winarning; Wulandari, Dwi (Unversitas Negeri Malang, 2017)
The purpose of this study investigated and understand impact of Problem-Based Learning on studentsâ€™ achievement in the economic course through lesson study. This kind a classroom action research in the subject of money and bank in order to participate in solving problems related materials. The Subject of this study is Grade 9 student in academic year 2016/2017. The implementation classroom action research conducted in two cycles comprising Planning, Implementation, observing, and reflection stages. The result of this study that Problem-Based Learning through lessons has been well implemented including the completeness of the learning tools and preparing the Lesson Plans before teaching on each teaching material. Based on the results of the implementation of lesson study using Problem-Based Learning model can be concluded that Problem-Based Learning through on the learning can improve student achievement.Keywords: Problem-Based Learning, Student Achievement, Classroom ResearchÂ DOI: 10.17977/um013v1i12017p001